Perbedaan Pengetahuan Kader Posyandu dan Ibu Balita Terkait Stunting serta Hubungannya dengan Kejadian Stunting pada Balita: Differences in Knowledge of Posyandu Cadres and Mothers of Toddlers Regarding Stunting and Its Association with Stunting Incidence in Toddlers - Rukmana, Erni; Fransiari, Muhammad Edwin; Damanik, Kanaya Yori; Nurfazriah, Latifah Rahman (Universitas Airlangga, 2024)
Background: Stunting, a condition where children fail to grow adequately for their age, is a significant public health issue in Indonesia. Health cadres play a vital role role as sources of information and knowledge for mothers of toddlers to prevent stunting. Objectives: To analyze differences in knowledge between Integrated Health Service Post (Posyandu) cadres and mothers of toddlers regarding stunting, and to examine the relationship between maternal knowledge of stunting and stunting incidence in children. Methods: This study was conducted in Medan Maimun Subdistrict, Medan City, from June to July 2024, using a cross-sectional design. A total of 68 cadres and 79 mothers of toddlers participated as respondents. Data were collected using validated questionnaires and analyzed using univariate analysis, independent sample t-test to compare knowledge levels between groups, And Spearman’s test to assess the relationship between maternal knowledge of stunting and stunting incidence. Results: Significant differences in stunting knowledge were found between health cadres and mothers of toddlers (p-value=0.003). Additionally, a significant relationship was observed between maternal knowledge of stunting and stunting incidence in children (p-value=0.034). Stunting incidence rates among children were 22.8% and 21.5%, respectively. Conclusions: Enhancing education and training for mothers of toddlers is essential to prevent stunting. The study also recommends strengthening the role of health cadres in delivering stunting-related education within the community.